Toxicity assessment of mycotoxins extracted from contaminated commercial dog pelleted feed on canine blood mononuclear cells. (April 2018) - Singh, Sanil D.; Sheik Abdul, Naeem; Phulukdaree, Alisa; Tiloke, Charlette; Nagiah, Savania; Baijnath, Sooraj; Chuturgoon, Anil A.
Abstract: Raw ingredients of pet food are often contaminated with mycotoxins. This is a serious health problem to pets and causes emotional and economical stress to the pet owners. The aim of this study was to determine the immunotoxicity of the most common mycotoxins (aflatoxin, fumonisin, ochratoxin A and zearalenone) by examining 20 samples of extruded dry dog food found on the South African market [10 samples from standard grocery store lines (SB), 10 from premium veterinarian lines (PB)]. Pelleted dog food was subjected to extraction protocols optimized for the above mentioned mycotoxins. Dog lymphocytes were treated with the extracts (24 h incubation and final concentration 40 μg/ml) to determine cell viability, mitochondrial function, oxidative stress, and markers of cell death using spectrophotometry, luminometry and flow cytometry. Malondialdehyde, a marker of oxidative stress showed no significant difference between SB and PB, however, GSH was significantly depleted in SB extract treatments. Markers of apoptosis (phosphatidylserine externalization) and necrosis (propidium iodide incorporation) were elevated in both food lines when compared to untreated control cells, interestingly SB extracts were significantly higher than PB. We also observed decreased ATP levels and increased mitochondrial depolarization in cells treated with both lines of feed with SB showing the greatest differences when compared to the control. This study provides evidence that irrespective of price, quality or marketing channels, pet foods present a high risk of mycotoxin contamination. Though in this study PB fared better than SB in regards to cell toxicity, there is a multitude of other factors that need to be studied which may have an influence on other negative outcomes. Highlights: Mycotoxins extracted from Premium brand and Standard brand pelleted dog food was cytotoxic to dog PBMCs. PBMC cell death and oxidative stress was enhanced in both categories of dog food. Study highlights the potential immunotoxicity of dog food regardless of purchasing channels.